1990
DOI: 10.1152/ajpcell.1990.258.6.c1108
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the transmembrane distribution of chloride in rat lymphocytes: role of Cl(-)-HCO3- exchange

Abstract: The purpose of the present experiments was to establish the factors that determine the intracellular Cl- concentration ([Cl-]i) of lymphocytes. Coulometric and isotope equilibration determinations indicated that [Cl-]i was in the range of 70-85 mmol/l cells. Since the membrane potential (Em) of these cells approximates -55 mV, [Cl-]i is severalfold higher than the level expected at electrochemical equilibrium (approximately 16 mM). This suggests that conductive pathways contribute marginally to the distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…11A). The reported value of intracellular Cl Ϫ concentration in lymphocytes is in the range of 50 -85 mM (39,40), and the extracellular Cl Ϫ concentration was ϳ108 mM under our experimental conditions, suggesting that extracellular Cl Ϫ influx also plays a significant role in the regulation of P2X 7 receptor-mediated splenic T cell shrinkage. In contrast, Auger et al (9) reported that the mode of P2X 7 receptor-mediated thymocyte death is necrosis/lysis via the phosphorylation of ERK1/2, rather than apoptosis.…”
Section: Discussionmentioning
confidence: 47%
“…11A). The reported value of intracellular Cl Ϫ concentration in lymphocytes is in the range of 50 -85 mM (39,40), and the extracellular Cl Ϫ concentration was ϳ108 mM under our experimental conditions, suggesting that extracellular Cl Ϫ influx also plays a significant role in the regulation of P2X 7 receptor-mediated splenic T cell shrinkage. In contrast, Auger et al (9) reported that the mode of P2X 7 receptor-mediated thymocyte death is necrosis/lysis via the phosphorylation of ERK1/2, rather than apoptosis.…”
Section: Discussionmentioning
confidence: 47%
“…The attempt to measure Cl Ϫ influx by using Cl Ϫ -sensitive fluorescent probe MQAE was unsuccessful because we were not able to distinguish the Cl Ϫ -dependent fluorescence change from the effect of leakage of MQAE (molecular weight 326) through the membrane pore formed in response to BzATP. The reported value of intracellular Cl Ϫ concentration in lymphocytes is in the range of 50 -85 mM (36,37), and the extracellular Cl Ϫ concentration is likely to be from 120 to 135 mM. Given the gradient of Cl Ϫ concentration across the membrane, opening a non-selective pore should result in Cl Ϫ moving into the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the abbreviations NC and KC are used, but not NCC and KCC. It is known that unidirectional Na + –Cl – coupled cotransport with 1:1 stoichiometry may be performed both by a single transport protein, like thiazide-sensitive Na + –Cl – cotransporter ( Gamba, 2005 ), and by two functionally coupled exchangers, NHE and Cl – /HCO 3 – ( Garcia-Soto and Grinstein, 1990 ; Hoffmann et al, 2009 ). The genetically identified cotransporters NKCC1 (SLC12A2) and KCC1 (SLC12A4) are expressed in U937 cells 1 , 2 .…”
Section: Methodsmentioning
confidence: 99%